1997
DOI: 10.1074/jbc.272.31.19253
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation and Inhibitory Domains of Hypoxia-inducible Factor 1α

Abstract: Hypoxia-inducible factor 1 (HIF-1) binds to cis-acting hypoxia-response elements within the erythropoietin, vascular endothelial growth factor, and other genes to activate transcription in hypoxic cells. HIF-1 is a basic helix-loop-helix transcription factor composed of HIF-1␣ and HIF-1␤ subunits. Here, we demonstrate that HIF-1␣ contains two transactivation domains located between amino acids 531 and 826. When expressed as GAL4 fusion proteins, the transcriptional activity of these domains increased in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
230
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 552 publications
(241 citation statements)
references
References 40 publications
8
230
0
3
Order By: Relevance
“…The levels of HIF-1a protein were then detected by western blotting with cells transfected with GFP acting as a negative control, whereas cells treated with 1% O 2 for 24 h acted as positive controls (Jiang et al, 1997). Results showed that overexpression of PI4KIIa, a novel player in tumor growth J Li et al PI4KIIa leads to a large accumulation of HIF-1a, while HIF-1a expression was also significantly induced by hypoxia (1% O 2 treated for 24 h).…”
Section: Pi4kiia Is Correlated With and Has A Crucial Role In Tumor Gmentioning
confidence: 99%
“…The levels of HIF-1a protein were then detected by western blotting with cells transfected with GFP acting as a negative control, whereas cells treated with 1% O 2 for 24 h acted as positive controls (Jiang et al, 1997). Results showed that overexpression of PI4KIIa, a novel player in tumor growth J Li et al PI4KIIa leads to a large accumulation of HIF-1a, while HIF-1a expression was also significantly induced by hypoxia (1% O 2 treated for 24 h).…”
Section: Pi4kiia Is Correlated With and Has A Crucial Role In Tumor Gmentioning
confidence: 99%
“…C-terminal transactivation domains can be found on both HIF-1α and HIF-1β (6)(7)(8)(9). The mouse HIF-1α gene the ubiquitous inducer of HIF-1α in all cells tested, other stimuli, such as insulin, IGF-1,2 and EGF, have also been shown to increase HIF-1α protein levels in certain cell types (18)(19)(20).…”
Section: A Major Mediator Of Angiogenesis Is Vascular Endothelial Gromentioning
confidence: 99%
“…Two mechanisms for this additional level of hypoxic regulation have been proposed. First, a region between NTAD and CTAD that inhibits transactivation was recently shown to form part of a binding site for the novel inhibitory factor, FIH-1 (18,21). According to this model, FIH-1 may dissociate from HIF-1␣ during hypoxia and thereby permit transactivation through CTAD.…”
mentioning
confidence: 99%
“…1). HIF-1␣ also contains an N-terminal transactivation domain (NTAD) that transactivates less effectively than CTAD alone; however, NTAD and CTAD together function synergistically (13,14,17,18). CH1 and CH3 are homologous Zn 2ϩ -binding domains of CBP͞p300 containing numerous cysteine and histidine residues (Fig.…”
mentioning
confidence: 99%